2020
DOI: 10.1097/eja.0000000000001324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-flow nasal oxygen during prolonged deep sedation on postprocedural atelectasis

Abstract: BACKGROUND Atelectasis is common in patients undergoing prolonged deep sedation outside the operating theatre. High-flow nasal oxygen (HFNO) produces positive airway pressure which, hypothetically, should improve lung atelectasis, but this has not been investigated. OBJECTIVE We investigated whether HFNO ameliorates postprocedural atelectasis and compared the influences of HFNO and facial oxygen by mask on postprocedural outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The feasibility of HFNO for NIBTS is also consistent with the results of bronchoscopy research ( 21 - 23 ) and with a shorter length of PACU stay. HFNO may have the advantage of causing minimal stress during airway management and preventing atelectasis ( 24 ). However, randomized controlled studies should be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of HFNO for NIBTS is also consistent with the results of bronchoscopy research ( 21 - 23 ) and with a shorter length of PACU stay. HFNO may have the advantage of causing minimal stress during airway management and preventing atelectasis ( 24 ). However, randomized controlled studies should be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of oxygen replace the nitrogen in the alveoli, leading to atelectasis [30,31]. Another study demonstrated that HFNCO reduces the occurrence of atelectasis during postoperative long-range deep sedation compared with a mask [32]. Because of the characteristics of hypoxic pulmonary vasoconstriction in pulmonary blood vessels, shunts may increase near alveoli with low oxygen concentrations, which further aggravates the imbalance of the ventilation/blood flow ratio.…”
Section: Discussionmentioning
confidence: 99%
“…These results were also observed across subgroups, including variations in the type of procedures, the FiO 2 , the hypoxemic profile of the patients, and the mode of propofol administration [35 && ]. Additional indications, such as computed tomography-guided hepatic tumor radiofrequency ablation [36], awake craniotomy [37], and hysteroscopy for assisted reproduction [38], also demonstrated favorable outcomes with the use of HFNO.…”
Section: Key Pointsmentioning
confidence: 99%